MOBILITAS SOSIAL PADA KELOMPOK DEWASA MUDA DI KELURAHAN KALABBIRANG KECAMATAN PATTALLASSANG KABUPATEN TAKALAR - Salam, Abd. Muhni (Pekerjaan Sosial, 2013)
AbstractThis research discussed about young-adulthood social mobility in Kalabbirang. The Research purposes are to obtain data and an overview of: characteristics of informants, channel of social mobility of informants, the support factors of social mobility informants, the inhibiting factors of social mobility informants, and the hope of informants. This study used a qualitative approach with descriptive methods and case study research. Informant numbers are 4 (four) persons who are determined by purposive sampling technique by fitted the criteria and objectives of the research. The results showed that the channel of social mobility that used by young-adulthood for their social mobility are religious institutions, educational institutions, and economic institutions. The support factors that affecting social mobility of young-adults Kalabbirang are structural factors, individual factors, social status, economic situation, political situation, free communication, division of labor, and the ease of access to education. The inhibiting factor of social mobility of young-adults Kalabbirang are poverty, socialization, and different interests. This research showed that young-adulthood social mobility Kalabbirang extremely increasing of social status and allow the other young-adults to do the same. Keywords: social mobility, young-adulthood, social status AbstrakPenelitian ini tentang mobilitas sosial pada kelompok dewasa muda di Kalabbirang. Tujuan penelitian untuk memperoleh data dan gambaran tentang: karakteristik informan, saluran mobilitas sosial informan, faktor pendorong mobilitas sosial informan, faktor penghambat mobilitas sosial informan, dan harapan informan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dan jenis penelitian studi kasus. Jumlah informan 4 (empat) orang yang ditentukan dengan teknik purposive sampling agar sesuai dengan kriteria dan tujuan penelitian. Hasil penelitian menunjukkan saluran mobilitas sosial yang digunakan oleh kelompok dewasa muda untuk melakukan mobilitas sosial adalah lembaga keagamaan, lembaga pendidikan, dan lembaga ekonomi. Faktor pendorong yang mempengaruhi mobilitas sosial dewasa muda Kalabbirang yaitu faktor struktural, faktor individu, status sosial, keadaan ekonomi, situasi politik, komunikasi yang bebas, pembagian kerja, dan kemudahan dalam akses pendidikan. Faktor penghambat mobilitas sosial dewasa muda Kalabbirang yaitu kemiskinan, sosialisasi yang kuat, dan perbedaan kepentingan. Hal ini menunjukkan bahwa mobilitas sosial kelompok dewasa muda Kalabbirang sangat baik dan lancar dan memungkinkan bahwa kelompok dewasa muda yang lain juga melakukannya. Kata kunci: mobilitas sosial, dewasa muda, status sosial